Evolutionary strategies for non-uniform deployment in wireless sensor networks. (7th September 2011) - Essaddi, Nejla; Hamdi, Mohamed; Habib, Sami; Boudriga, Nourreddine
Wireless sensor networks (WSNs) have been the subject of an important development during the last years. Most of the applications deployed over WSNs require strong coverage requirements, especially those related to the detection and tracking of distributed events. In this paper, we use the Voronoi tessellation of the region of interest to formulate and solve an evolutionary optimisation problem modelling the activation of the deployed sensors. The major idea behind our approach is to adapt the spatial sensor distribution to the local probability of target presence. We show, through the results of our experiments, that our method allows a non-uniform deployment of the sensor nodes, which is better suitable for tracking applications.